Studies on optical and electrical properties of green synthesized TiO2@Ag core-shell nanocomposite material. (13th April 2018) - Ganapathy, M; Senthilkumar, N; Vimalan, M; Jeysekaran, R; Potheher, I Vetha
Abstract: Newly adopted green approach has been used to synthesize pure titanium dioxide (TiO2 ) nanoparticles (NPs) and silver deposited titanium dioxide (TiO2 @Ag) core–shell nanocomposite (CSNC) from Nigella Sativa (black cumin) seed extract for the first time. The phytochemicals available in Nigella Sativa (NS) seed extract acts as reducing agent in the formation of nanoparticles as well as nanocomposite. The morphology, crystal structure, particle size and phase composition of green synthesized TiO2 NPs and TiO2 @Ag CSNC are investigated by High Resolution Transmission Electron Microscopy (HRTEM), Field Emission Scanning Electron Microscopy (FESEM), Powder x-ray diffraction (PXRD), FT–Raman and Fourier Transform Infrared spectroscopy (FT-IR). The red shift in (from 333 nm to 342 nm) UV–Vis spectrum confirmed the deposition of Ag on TiO2 . The reduced intensity peaks of Photoluminescence spectra (PL) also indicate the deposition of Ag on TiO2 . Further the electrical properties of pure TiO2 and TiO2 @Ag CSNC have studied by dielectric studies and ac conductivity measurements. The dielectric constant and the dielectric loss of TiO2 @Ag CSNC are better than pure TiO2 . From these improved results, the green synthesized TiO2 @Ag CSNC from NS seed extract is may be a suitable material for device fabrication in the visible region.